Charitable activities of representatives the German minority in Kharkiv (XIX – beginning of the XXth century) - Філатова, Ольга (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
The article deals with an issue of the charity activity of the Kharkiv German national community in ХІХ – early XX century, in the context of their active participation in the social life of the city. Particular attention is devoted to the process of establishment and evolution of national charitable society in the course of ХІХth century. The interrelation of ethnic Germans`s material donations and contributions, within regional state public charities and individual ones, with the process of development of education, medicine and social protection of Kharkiv region is under analysis.